ANALISIS KESIAPAN PENERAPAN REKAM MEDIS ELEKTRONIK (RME) DI RUMAH SAKIT MITRA SIAGA TARUB TEGAL - Zahrasita Nur Indira; Aep Saepulloh (Bajang Institute, 2025)
Electronic Medical Records have many benefits in health services. At this time, Mitra Siaga Tarub Tegal Hospital will implement services with electronic medical records as a whole, both outpatient, inpatient, emergency and other supports to increase efficiency and improve service quality and ensure patient safety. Therefore, an assessment must be carried out on the readiness of RME implementation. In this case, it can identify which are priorities and help shape operational functions in supporting the optimization of RME implementation. The purpose of this study is to analyze the readiness of the implementation of RME at Mitra Siaga Tarub Tegal Hospital. Using a case study method with a qualitative approach. This research was conducted at Mitra Siaga Tarub Tegal Hospital. This research will start from December 2024 to January 2025. Using the purposive sampling method in the selection of the informants involved. This study obtained results that show that it is quite ready in the organizational culture. Knowledge of the implementation of RME has been disseminated to the entire hospitalia community and there are still obstacles related to services that are still using manuals because they have not been integrated. Mitra Siaga Tarub Tegal Hospital has a very clear goal in implementing RME. The informant is confident that he can succeed in changing the manual medical record system to electronic one implemented in hospitals. The readiness of human resources (HR), infrastructure and infrastructure facilities are ready, this can be seen from the positive response of the hospitalia community in the use of RME. The implementation of RME is going well although there are still some obstacles. The readiness of RME implementation needs to be improved as the development of RME progresses, both from organizational culture, governance and leadership readiness, in terms of human resource readiness and infrastructure readiness